Synthesis and characterisation of (Alkoxybenzimidazolin-2-ylidene) palladium complexes: the effect of ancillary ligands on the behaviour of precatalysts - Baker, M.; Brown, David; Simpson, P.; Skelton, B.; White, A. (Wiley-VCH Verlag GmbH & Co, 2009)
A series of new N-heterocyclic carbene (NHC)-palladium(II) complexes bearing electron-rich benzimidazolin-2-ylidene ligands are described and structurally and spectroscopically characterised. These (benzimidazolin-2-ylidene)palladium complexes bear butoxy groups to increase the solubility and perhaps influence the catalytic activity by increasing the electron density around the metal centre. The effect of varying the ancillary ligands is investigated, although these ligandsdo not appear to significantly alter the activity of the complexes as precatalysts. Preliminary studies indicate the complexes act as precatalysts with moderate activity in the Mizoroki-Heck and Suzuki-Miyaura coupling reactions.